Understand lighting for video, film and photography - Luft, Greg; First Light Video Publishing (Venice, CA. : First Light Video Publishing)
This fast-paced program covers the importance of light for quality images in any medium. Includes dozens of creative tips for using natural light, existing interior light, standard lighting fixtures and professional lighting equipment. Also covers the use of gels, reflectors, filters, and other tools to create interesting images and programs
Title from title screen
Keywords: Cinematography -- Lighting; Photography -- Lighting; Video recording -- Lighting